The Conservation Multiplier - Bård Harstad (Center for Economic Studies and ifo Institute (CESifo), 2020)
Every government that controls an exhaustible resource must decide whether to exploit it or to conserve and thereby let the subsequent government decide whether to exploit or conserve. This paper develops a theory of this situation and shows when a small probability that some future government will exploit a resource leads to a domino effect with rapid exploitation. This effect leads to a multiplier that measures how a small change in parameters can have large effects. The multiplier is especially large if the government is powerful now but unlikely to be in power later. The multiplier also permits dramatic returns on lobby contributions contingent on exploitation – or on compensations contingent on conservation – when these offers are expected to continue. To best take advantage of the multiplier, I show how and when compensations should be offered to the president, the party in power, the general public, or to the lobby group.
Keywords: D72; C73; Q57; O13; 330; dynamic games; exhaustible resources; deforestation; political economy; lobbying; conservation; PES; REDD+.